Citizen Science in Postsecondary Education: Current Practices and Knowledge Gaps. (5th January 2022) - Vance-Chalcraft, Heather D; Hurlbert, Allen H; Styrsky, Jennifer Nesbitt; Gates, Terry A; Bowser, Gillian; Hitchcock, Colleen B; Reyes, Michelle Anne; Cooper, Caren B
Abstract: Citizen science involves the public in science to investigate research questions. Although citizen science facilitates learning in informal educational settings, little is known about its use or effects in postsecondary (college or university) settings. Using a literature review and a survey, we describe how and why citizen science is being used in postsecondary courses, as well as the impacts on student learning. We found that citizen science is used predominantly in biologically related fields, at diverse types of institutions, to improve student engagement and expose students to authentic research. Considerable anecdotal evidence supporting improved student learning from these experiences exists, but little empirical evidence exists to warrant any conclusion. Therefore, there is a need to rigorously assess the relationship between citizen science participation and postsecondary student learning. We highlight considerations for instructors planning to incorporate citizen science and for citizen science projects wanting to facilitate postsecondary use.